Title IX coordinators as street-level bureaucrats in U.S. schools: Challenges addressing sex discrimination in the #MeToo era - Elizabeth J. Meyer; Andrea Somoza-Norton; Natalie Lovgren; Andrea Rubin; Mary Quantz (Arizona State University, 2018)
Sex discrimination in educational contexts is an ongoing problem despite the passage of Title IX in 1972. Many schools have not aligned their policies with new laws protecting students from bullying and harassment, and many professionals are unaware of their new obligations in regards to new state regulations. This article presents the findings from semi-structured interviews with 10 participants reporting on the roles and responsibilities of Title IX coordinators in their K-12 school districts. Title IX coordinators were difficult to locate and recruitment was a challenge in this study. However, our findings indicate a strong alignment with Lipsky's concept of "street-level bureaucrats" (1971, 2010). We found that these school administrators had autonomy and discretion in interpreting and enacting their duties, however they lacked time, information, and other resources necessary to respond properly to the stated duties in their position. They reported spending very little time on Title IX-related duties, many felt under-supported and under-prepared, and few had comprehensive understanding of their responsibilities. We conclude with recommendations for policy and practice regarding the training and supports of Title IX coordinators and related gender equity efforts in K-12 schools.